THE IMPACT OF HIGH INTAKE OF SUGARY DRINKS ON ABDOMINAL OBESITY AND BLOOD GLUCOSE OF YOUNG ADULTS IN DISTRICT PESHAWAR (The Research of Medical Science Review, 2024)
The current cross-sectional study was designed to evaluate the impact of high intake of sugary drinks on abdominal obesity and blood glucose of young adults aged 19-25y in district Peshawar. The study was carried out at district Peshawar. A total of 200 young adults comprising of 100 males and 100 females were randomly selected. Data regarding socio demographic characteristics, anthropometric parameters, bio chemical parameters, physical activity, 24 hrs. dietary recall as well as consumption of sugary drinks were collected using a pre-planned questionnaire. After successful data collection the data was analyzed with the help of SPSS (Statistical package for Social Science). The study concluded that the Mean age of Male and female student was 24±2.15 (years) and 23.2±2.5 (years). The mean weight of male and female was 73.84±7.79 (kg) and 60.30±7.79 (kg). The Mean Height of male and female was 171.6±11.5 (cm) and 163.6±9.6 (cm). The Mean Body mass index of male and female was 24.27±2.21 and 22.05±2.78. Majority of the male (65%) and females (85%) were normal. The mean of waist circumference of male and female was 96.74+7.07and 81.10±7.83 respectively. Whereas Male (76%) and females (87%) were normal according to waist circumference were normal. The mean blood glucose level of male and female was 93.50 ±8.67 (g/dl) and 83±8.39 (g/dl). Majority of the males (82%) and females (83%) had normal blood glucose level. Majority of the males (18%) and females (14%) were not having any physical activity, whereas fast pace of walking was recorded for Males (13%) and females (16%) respectively. Soda drinks were never consumed by male (24%) and female (25%). Some of the males (19%) and females (17%) had consumed non soda drinks up to 3 days in a week. Sweet tea was consumed up to 6 days in a week by males (25%) and females (30%). Some of the males (24%) and females (24%) were consuming sweetened coffees on daily basis. A significant difference (p>0.05) was recorded for the intake of sweetened tea in relation to the body mass index of the subjects. A significant variation (p>0.05) was observed for the intake of soda drinks in relation to the level of blood Glucose of the subjects.